Rethinking housing between concepts and practical applications: A rights and capabilities based approach (Desenvolvimento em Questão, 2026)
Due to its close connection to social well-being, housing intensifies complex debates around rights, citizenship, and housing provision. This article aims to shed light on these discussions by offering a more structured analysis of rights-based approaches in the housing context. It begins with the philosophical distinction between natural and socially constructed rights, proposing a viable alternative grounded in the Capabilities Approach of Amartya Sen and Martha Nussbaum. In this framework, citizenship is presented as a bridging concept, capable of linking abstract philosophical discourse on rights to their implementation in specific political contexts. To operationalize this proposal, the article draws on Thomas Marshall’s categorization of civil and social rights, reinterpreted here as a contemporary distinction between legally enforceable and programmatic rights in the housing domain. This allows for an analysis of the intersections between individual rights and collective responsibilities. The article demonstrates that one can reject the notion of natural or universal rights to housing while still advocating for well-defined, enforceable legal rights that guarantee minimum housing conditions for vulnerable populations. This dual perspective highlights the complexity of the topic, calling for an approach that balances ethical foundations with legal and political pragmatism, particularly regarding the social and structural implications of housing policies.
Keywords: Right to housing; Socially constructed rights; Capabilities Approach; Amartya Sen; Martha Nussbaum